2018
DOI: 10.9734/ajaees/2018/43006
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Perception towards Harmful Effects of Climate Change on Agriculture

Abstract: The main objectives of the study were to determine farmers' perception towards harmful effects of climate change on agriculture in Bangladesh and to identify the factors that influence farmers' perception towards harmful effects of climate change. The study was conducted in four villages under Kazipur upazila of Sirajgonj district. Data were collected by using interview schedule from randomly selected 113 respondents. The findings revealed that an overwhelming majority (89.4%) of the respondents had lower to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Favorable perception influence people to use technology. [16] revealed that farmers favorable perception influence them to use adaptation strategy which is similar to the present study.…”
Section: The Contribution Of the Selected Characteristics Of The Respsupporting
confidence: 89%
“…Favorable perception influence people to use technology. [16] revealed that farmers favorable perception influence them to use adaptation strategy which is similar to the present study.…”
Section: The Contribution Of the Selected Characteristics Of The Respsupporting
confidence: 89%
“…Education may help the beneficiaries to broaden their outlook towards utilizing of SELP loan. Similar findings were observed in the case of [14,15] who mentioned that education is an important factor to uplift socio-economic condition of the rural farmers through the use of smart adaptation strategies. With the increase of age, a man increases his experience and knowledge which might help to utilize SELP loan more effective way to increase their socio-economic condition [16,17].…”
Section: Contribution Of the Selected Characteristics Of The Selp Ben...supporting
confidence: 85%
“…However, sometimes the reverse condition also happened that is higher the involvement lower the success in an activities. Attitude is also an important item to accept a technology or loan for improving socio-economic condition [16][17][18]. The study findings indicate favorable attitude of the beneficiaries lower the problem face socioeconomic development activities.…”
Section: Relationship Between the Selected Characteristics Of The Sma...mentioning
confidence: 85%